ANALISA TERHADAP PENGGUNA APLIKASI SHOPEE YANG MENGALAMI KETERLAMBATAN PEMBAYARAN SPAYLATER - Yuyun Yulianah; Mumuh M Rozi; M. Rendi Aridhayandi; Muhammad Fahmi Anwar (Jurnal Hukum Mimbar Justitia, 2022)
SPaylater is a feature in shopee e-commerce that is used as a payment method that provides loans for its users, to make transactions on e-commerce in the shopee application. The use of the SPayLater feature imposes terms and conditions that must be met. However, users often ignore these terms and conditions, resulting in legal consequences. The problems studied are: (1), what are the factors that cause delays in payment of SPayLater users to consumers?, (2) What is the impact of late payments of SPayLater on the shopee application?, (3) What are the responsibilities of the parties?. The problem approach used in this research is normative juridical which uses the law or law approach method that exists in library data or secondary data. Based on the results of the study, it can be seen that the legal arrangement that regulates SPayLater in e-commerce shopee is the Agreement as regulated in Article 1313 of the Civil Code. The impact if the shopee e-commerce user delays the payment, namely the user's shopee account will be frozen by the Shopee and the user's personal data is then recorded in the financial information service system which can prevent users from getting financing from the bank as well as other companies. Â Keywords: Cause Factor, Delay, Impact of SPayLater.